Determinant of state-owned enterprises financial health: Indonesia empirical evidence - Nur Sayidah; Aminullah Assagaf; Bayu Taufiq Possumah (Cogent Business & Management, 2019)
This research is motivated to study the phenomenon of the financial health of state-owned enterprises (SOEs) who are healthy but still dependent on government subsidies. Based on these phenomena, the aim of this study is to determine the factors that affect the company's financial health. In order to achieve this aim, the present research will employ the purposive sampling method of seven SOEs with observations during the last 11 years. The data analysis employed involves the use of linear regression model and its management through software SPSS-Amos 23. As a result, the study found that subsidy is significant and negatively affects financial health, which means that the financial health of the SOEs is getting down when funding is still maintaining subsidy every year. Instead, financial health would be enhanced if the government limits the subsidies gradually and gives broad authority to decide on the pricing structure and control of resources to support the cost of efficiency. The study also found that firm size strengthens the link between subsidies to financial health with a positive coefficient and is exhibited significantly, which means that the larger the firm size, the stronger the effect of subsidies on the financial health SOEs. This means that the SOEs that have a good asset capability tend to have a better financial health, especially because efficient opportunities are supported by the control of resources and a more economical business scale.
Keywords: 650; financial health; earnings management; subsidy